How hepatitis C virus invades hepatocytes: The mystery of viral entry - Zhu, Yong-Zhe (World journal of gastroenterology : WJG, 2014)
Hepatitis C virus(HCV)infection is a global health problem,with an estimated 170 million people being chronically infected.HCV cell entry is a complex multi-step process,involving several cellular factors that trigger virus uptake into the hepatocytes.The high-density lipoprotein receptor scavenger receptor class B type I,tetraspanin CD81,tight junction protein claudin-1,and occludin are the main receptors that mediate the initial step of HCV infection.In addition,the virus uses cell receptor tyrosine kinases as entry regulators,such as epidermal growth factor receptor and ephrin receptor A2.This review summarizes the current understanding about how cell surface molecules are involved in HCV attachment,internalization,and membrane fusion,and how host cell kinases regulate virus entry.The advances of the potential antiviral agents targeting this process are introduced.